Nano-based ceramic surgical blade accelerates wound healing - Ada, Fatih; Gümüş, Erkan; Kasımzade, Ferit (Journal of Surgery and Medicine, 2021)
Background/Aim: Many factors affect the results of a surgical operation, one of which is the harmony of the materials used during surgery with the tissue. Zirconia is a material with antimicrobial properties, high surface sensitivity and robustness. This study was conducted to observe the acute and subacute effects of the nano-based zirconia surgical blade on living tissue. Methods: The study was conducted after approval was granted by the Sivas Cumhuriyet University Animal Experiments Local Ethics Committee with the decision number 65202830-050.04.04-33. A total of 16 rats were used in the study. Eight were incised with classic steel surgical blade and eight, with nano-based zirconia surgical blade. A total of 4 incisions were performed to each rat and the incisions were closed with 3.0 polypropylene suture. Tissue samples were obtained from the incisions on day 0, 3, 7 and 21, and examined histologically. Results: The epidermis layer thickness on days 7 and 21 (P=0.030, P=0.025), the dermis layer thickness on days 3 and 7 (P=0.035, P=0.030), muscle layer thickness on days 7 and 21 (P=0.030, P=0.025) were significantly increased and inflammatory cells were significantly less on days 3, 7 and 21 (P=0.030, P=0.020, P=0.025) in the nano-ceramic surgical blade compared to the other group. Collagen tissue density was significantly higher in favor of the nano-ceramic blade on the 3rd and 7th days (P=0.025, P=0.020). Conclusion: Nano-based zirconia surgical blade has been shown to have positive effects on wound healing. The use of nano-based zirconia surgical blade should be kept in mind in patient groups with wound healing problems.